2003
DOI: 10.4314/tjpr.v2i1.14582
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine reduces urinary excretion of cloxacillin when it is administered concurrently with ampicillin-cloxacillin combination

Abstract: Purpose: To investigate a possible effect of chloroquine on urinary excretion of cloxacillin when chloroquine is administered concurrently with ampicillin-cloxacillin combination. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The pattern of results obtained and the half-life values in this study correlate with in vivo reports in earlier studies [ 4 6 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The pattern of results obtained and the half-life values in this study correlate with in vivo reports in earlier studies [ 4 6 ].…”
Section: Discussionsupporting
confidence: 91%
“…The possible effect of chloroquine on the urinary excretion of cloxacillin when co-administered with ampicillin–cloxacillin was also investigated earlier in eight healthy adult volunteers [ 6 ]. A significant reduction (64 %) in the urinary excretion of cloxacillin was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of interactions between antimalarials, particularly those belonging to the quinoline class, and antibiotics has been studied extensively in the past two decades (Babalola et al, 2002(Babalola et al, , 2003(Babalola et al, , 2009Abreu et al, 2014;Falade et al, 2016). Malaria is immunosuppressive.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, penicillin antibiotics have been reported to demonstrate in vivo and in vitro interactions with certain antimalarial agents (Babalola et al, 2003(Babalola et al, , 2009Falade et al, 2016). Documented interactions include reduction in bioavailability of penicillins (ampicillin and cloxacillin) by 40-70 % after oral co-administration with quinine and chloroquine in healthy patients (Ali, 1985;Babalola et al, 2003;Falade et al, 2016). Other studies reported similar interactions with proguanil and artesunate (Babalola et al, 2002(Babalola et al, , 2009, suggesting that pharmacokinetic drug interaction is likely occurring at the absorption phase (Palleria et al, 2013).…”
Section: Introductionmentioning
confidence: 99%